PENYULUHAN PEMBASMIAN HAMA TIKUS PADA TANAMAN SAYURAN PADA KELOMPOK TANI DI KAMPUNG PUTRA BULU DESA AWANG BANGKAL KABUPATEN BANJAR - Wasdiyanta i22026; Ahmad Baparki; Rohansyah (Fakultas Pertanian UVAYA Banjarmasin, 2026)
In fruit vegetables such as cucumbers, tomatoes and long beans, mice often eat fruit that is still young or even ready to be harvested, thereby destroying the selling value. The aim of this outreach is to provide education to the public regarding the losses from rat pest attacks. provide how to handle it and provide examples of the use of medicines, the method used is face to face contact with farmers. The results obtained are that farmers understand the dangers of rat pest attacks on vegetable crops